Encapsulated Fe3C boosted electrocatalytic performance for oxygen reduction reaction of N-doped carbon nanotube - Jun Dong; Qiqi Jiao; Hao Wang; Hong Wang; Yi-ke Ren (Heliyon)
The shortcomings of precious metal based catalysts have limited the development of novel energies. So, developing low-cost and high performance transition metal based catalysts is one of the most feasible way to substitute the precious metal based catalysts. In all of the developed catalysts for oxygen reduction reactions (ORR), the iron-based nitrogen doped carbon nanotube (N-CNT) show great promise. In this paper, N-CNT with Fe3C encapsulated based catalysts (Fe3C@N-CNT) were synthesized. The encapsulation structure of Fe3C@N-CNT was confirmed by HAADF-STEM, XANES, XPS, XRD, SEM and other methods. XANES tests show that the doped nitrogen of Fe3C changed the length of Fe-C bond and furtherly influenced the electron transfer between encapsulated Fe3C and outer layer N-CNT. Electrochemical tests showed that the half-wave potential and onset potential ORR of 750 °C calcined Fe3C@N-CNT were 90 mV higher than that of 20 wt% Pt/C. The additional electric field between Fe3C and N-CNT modulated the C-N bond of surface N-CNT and enhanced the catalytic performance for ORR. This paper reveal that constructing encapsulated additional electron providing center is an effective way to design high performance catalysts.